Ano-rectal malformations in pigs: a report of a striking case in an eight-week-old piglet (a case report) (2011)
Anorectal malformations are rare congenital disorders in animals. In swine, atresia ani occurs with an incidence of 0.1—1.0 % and it is the most important cause of intestinal obstruction in that species. This paper reports a striking case of atresia ani et recti in an eightweek- old piglet. The surgical management and preventive measures are discussed